Experimental studies on the vortex-induced forces of a 4:1 rectangular cylinder and two typical bridge girders. Issue 3 (February 2020) - Li, Ming; Sun, Yanguo; Lei, Yongfu; Li, Mingshui
Wind tunnel tests were performed on a 4:1 rectangular (REC) cylinder, a trapezoidal (TRA) girder, and a typical streamlined (STR) box girder to investigate the vortex-induced forces and their spanwise correlations. First, using the free vibration technique, the vortex-induced vibration responses and the Strouhal number were investigated at different Scruton numbers and attack angles. Then, the mean and standard deviations of the vortex-induced pressure coefficients of the three models were analyzed through simultaneous pressure measurements. The power spectral density and the spanwise correlation of vortex-induced pressures at some typical points were also studied. Finally, the spanwise correlations of vortex-induced forces acting on the three models in the cases of different vibration amplitudes and attack angles were investigated. The results show that the attack angle has a significant effect on the vortex-induced pressure distributions for the three types of girders. The second frequency components of the vortex-induced pressure occur near the trailing edge of the upper surface for the three types of sections. The correlation of vortex-induced force decreases with the increase in the oscillation amplitude for the REC model, but becomes larger for the TRA and STR models. With the increase in the attack angle, the spanwise correlations of vortex-induced forces on the three sections become weaker, especially for the REC model.